The Axiology Aspect should be Encouraged, Not the Jargon as Kampung Inggris Sawai - Thobias Sarbunan (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Kampung Inggris study aimed to pinpoint distinctive features of the conceptual and methodological underpinnings of the English course. This article's chronology was primarily based on information on incentives for community service in Sawai village and the inability that preceded the service. It was demonstrated that the expansion of organizations that provide English language courses was not only reliant on the objectives and linguistic skills of the initiator.